2018
DOI: 10.1159/000487265
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy: A European Perspective in the Corticosteroid Treatment

Abstract: Background: IgA nephropathy (IgAN) is detected in Europe in 22% of glomerular diseases diagnosed by biopsy. The frequency of IgAN as cause of ESRD in Europe has increased in the last decades, accounting for 35% of young and adult transplanted patients. These data justify the interest for risk factors and a possible therapeutic approach. Summary: Insight into a European perspective of IgAN was allowed by the multicenter study VALIGA, on 1,147 patients, almost all Caucasians, with follow-up of 4.7 years. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, corticosteroids inhibit c-Jun, Fos, and NF-κB pathways, consequently inhibiting inflammatory responses. Due to these corticosteroid effects, they are widely used as in the treatment of autoimmune diseases [ 94 ]. Early studies reported that corticosteroids may improve renal outcomes in these diseases, showing that patients treated with corticosteroids have improved 5-year renal survival and reduced proteinuria, compared with patients treated with supportive therapy [ 95 ].…”
Section: Therapeutic Strategies For the Treatment Of Iganmentioning
confidence: 99%
“…Additionally, corticosteroids inhibit c-Jun, Fos, and NF-κB pathways, consequently inhibiting inflammatory responses. Due to these corticosteroid effects, they are widely used as in the treatment of autoimmune diseases [ 94 ]. Early studies reported that corticosteroids may improve renal outcomes in these diseases, showing that patients treated with corticosteroids have improved 5-year renal survival and reduced proteinuria, compared with patients treated with supportive therapy [ 95 ].…”
Section: Therapeutic Strategies For the Treatment Of Iganmentioning
confidence: 99%
“…The role of corticosteroid intervention for IgAN remains debated [21][22][23]. In the STOP-IgAN trial, immunosuppressive therapy for high-risk IgAN patients did not signi cantly improve the outcome, and more adverse effects were observed [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin A nephropathy (IgAN) is the most common type of primary glomerulonephritis globally, which is a major cause of end-stage renal disease [1,2] . Moreover, approximately 30%-40% of kidney biopsies confirm IgAN, with frequencies in Asia ranging from 22% to 39%, which is higher than those observed in Europe [3,4]. IgA-dominant immunoglobulin deposition in the glomerular mesangial area of the kidney is considered the main cause of IgAN; however, the specific pathogenesis underlying IgAN remains to be elucidated [5,6].…”
Section: Introductionmentioning
confidence: 99%